The Effectiveness of Disaster Health Management in Families with Chronic Illnesses on Preparedness for Earthquake Disasters - Suciana, Fitri; Agustiningrum, Ratna; Pramono, Cahyo (Media Keperawatan Indonesia, 2025)
The World Health Organization (WHO) identifies vulnerable groups during natural disasters as including children, pregnant women, the elderly, individuals with chronic illnesses or immune disorders, and those suffering from malnutrition. Individuals with chronic illnesses are particularly vulnerable during disasters due to health condition disruptions and interruptions in routine healthcare access caused by the disaster. Consequently, these groups face an elevated risk of infectious diseases, respiratory problems, skin integrity issues, and even mortality compared to the general population. According to WHO, chronic illnesses include diabetes mellitus, hypertension, stroke, heart disease, and kidney failure. The family plays a crucial role in mitigating these challenges through preparedness, which involves providing information to family members, influencing timely and appropriate decision-making, and serving as a source of social support. Therefore, research is necessary to evaluate the role of families in managing health among members with chronic illnesses. This encompasses assessing the family’s knowledge and skills in health management and developing strategies to enhance these competencies to improve health outcomes for chronic illness-affected families.